Laboratory Study of Steel Slag Used for Stabilizing Expansive Soil (University of Khartoum Engineering Journal, 2022)
This paper presents an experimental study in stabilization of expansive soil using Steel Slag (SS). Experimental program was conducted to evaluate the influence of Steel Slag on improving the engineering properties of expansive clay. A series of tests to measure consistency limits, free swell index, compaction parameters and unconfined compressive strength of natural and stabilized soils. The effectiveness of adding 0, 5, 10, 15, 20, and 30 percentages of SS to the soil was studied. Comparing the results obtained for the natural and stabilized soils, revealed that SS has significant effect on strength parameters and considerable improvement in plasticity and swelling properties. Addition of SS to the soil increased the dry density and decreased the optimum moisture content as well as increased the unconfined compressive strength. It is concluded that the use of steel slag to enhance properties of expansive soil is successful and beneficial.
Keywords: Expansive soil; improving; steel slag; strength; swelling.